Pengaruh Penggunaan Strategi LRD (Listen-Read-Discuss) dan Penguasaan Kosakata bahasa arab Terhadap Kemampuan Membaca Siswa Kelas 8 MTs Nurul Huda Malangnengah Tangerang - Fajar Aprilianto; Moch Muizzuddin; Zaki Ghufron (Saintifika Islamica, 2022)
Reading is an ability that must be possessed by students, especially in language learning, in learning Arabic. The lack of teachers in mastering learning strategies and the lack of students in mastering Arabic vocabulary can both be the cause of the problem of the lack of students' reading skills, it has become a must for teachers to master several learning strategies, especially strategies that are suitable for learning to read so that learning does not become boring and the objectives of learning to read can be achieved well. One of the strategies that are suitable for learning to read is the LRD Strategy (Listen-Read-Discuss) because this strategy can improve reading skills as well students should memorize a lot of mastering Arabic vocabulary to improve their reading skills so that the objectives of learning to read can be achieved properly.